Potential of bioactive compound of Cyperus rotundus L. rhizome extract as inhibitor of PD-L1/PD-1 interaction: An in silico study - Nafisah, Wirdatun; Fatchiyah, Fatchiyah; Widyananda, Muhammad Hermawan; Christina, Yuyun Ika; Rifa’i, Muhaimin; Widodo, Nashi; Djati, Muhammad Sasmito (Agriculture and Natural Resources, 2022)
Importance of the work: The mechanism of cancer escape from immune system elimination is mediated by the PD-L1/PD-1 protein interaction. Objectives: To investigate the potential of a bioactive compound of Cyperus rotundus L. rhizome extract (CRE) as an inhibitor of PD-L1/PD-1 interaction. Materials & Methods: The plant extraction was carried out using ethanol, and the bioactive compounds of CRE were identified using liquid chromatography-high resolution mass spectrometry. Three CRE bioactive compounds—NCGC00380624-01 (Cmpd1), tetramethylcyclopentadiene (Cmpd2), and luteolin (Cmpd3)—were used for further analysis, consisting of biological activity prediction using the PASS server, molecular docking through Autodock Vina in PyRx and molecular dynamics simulation using the YASARA software. All analyses were compared with BMS-202 as a control inhibitor. Results: PASS prediction showed several activities of the compounds related to cancer, including the HIF-1α expression inhibitor. Furthermore, molecular docking analysis showed the potential inhibition of the PD-L1 protein by Cmpd2 and Cmpd3. The inhibition may be attributed to the involvement of key residues between BMS-202 and the PD-L1 protein, such as Tyr56, Ala121, Met115 and Tyr123. The binding energy of BMS-202 was the lowest, followed by Cmpd3, Cmpd2 and Cmpd1 (-11.2 kcal/mol, -8.9 kcal/mol, -6.2 kcal/mol and -4 kcal/mol, respectively). Molecular dynamics simulation confirmed that the most stable interaction was Cmpd3/PD-L1, whereas the most unstable interaction was Cmpd1. Main finding: The CRE bioactive compounds could be considered as potential inhibitors of PD-L1/PD-1 interaction. This inhibition could be expected to reactivate T cells and enhance their ability to eliminate cancer cells.